PENERAPAN HIDROPONIK DEEP FLOW TECHNIQUE SEBAGAI EDU-CENTER DI DESA KAPI, KUNJANG, KEDIRI - Tsamroh, Dewi Izzatus; Putri, Widyarini Susilo; C., Muhammad Ilham Abednego Elsa; Fadillah, Rahmat Fahil; Brilliandy, Hikmal Akbar (Jurnal Pengabdian Masyarakat Khatulistiwa, 2022)
ABSTRACTThe partner in this community service activity is Kapi Village, which is in the Kunjang District, Kediri Regency. According to a service team survey, Kapi Village has a potential that can be developed, which is in the tourism sector. This is also in accordance with the idea of a joint farmer group (gapoktan) who wants agro-tourism since 2020. However, the problems faced by partners are related to the tourism village development strategy which is still lacking to pioneer a tourist village. The solution that can be offered by the service team is to apply appropriate technology in the form of hydroponic deep flow technique (DFT). The method of implementing service activities is carried out through surveys, giving post-test and pre-test, providing socialization and training, to mentoring. The results of community service activities show that the community already has knowledge related to appropriate hydroponic technology. Furthermore, the DFT hydroponic installation is installed in one part of the grape picking garden as an edu-center which acts as a medium for learning to grow crops without using soil media.Keywords: Community Empowerment, Hydroponics, Deep Flow Technique, Edu-center, Tourism VillageABSTRAKMitra dalam kegiatan pengabdian masyarakat ini adalah Desa Kapi yang berada di wilayah Kecamatan Kunjang, Kabupaten Kediri. Menurut survei tim pengabdi, Desa Kapi memiliki potensi lain yang dapat dikembangkan, yakni di bidang pariwisata. Hal ini juga sesuai dengan gagasan gabungan kelompok tani (gapoktan) yang menginginkan adanya agrowisata sejak tahun 2020. Akan tetapi, permasalahan yang dihadapi mitra adalah terkait dengan strategi pengembangan desa wisata yang masih kurang untuk merintis sebuah desa wisata. Solusi yang dapat ditawarkan oleh tim pengabdi adalah dengan menerapkan teknologi tepat guna berupa hidroponik deep flow technique (DFT). Metode pelaksanaan kegiatan pengabdian dilakukan melalui survei, pemberian post-test dan pre-test, pemberian sosialisasi dan pelatihan, hingga pendampingan. Hasil kegiatan pengabdian masyarakat menunjukkan bahwa masyarakat telah memiliki pengetahuan terkait dengan teknologi tepat guna hidroponik. Selanjutnya instalasi hidroponik DFT dipasang di salah satu bagian kebun petik buah anggur sebagai edu-center yang berperan sebagai media pembelajaran bercocok tanam tanpa menggunakan media tanah.Kata Kunci: Pemberdayaan masyarakat, Hidroponik, Deep Flow Technique, Edu-center, Desa wisata.